Restructuring for Sustainability: How Organizational Culture Drives Green Strategic Initiatives - Saratian, Eko Tama Putra; Akbar, Taufik; Suparno; Mukhtar, Saparuddin (SAFE-Network, 2025)
Organizational restructuring for sustainability is increasingly recognized as a strategic imperative rather than a compliance-driven adjustment. This study employs a Systematic Literature Review (SLR) using the PRISMA framework to analyze peer-reviewed research from Scopus, Web of Science, and ScienceDirect, focusing on publications between 2015 and 2025. The findings emphasize that organizational culture acts as a catalyst in sustainability transitions, influencing leadership effectiveness, employee engagement, and the adaptability of structural changes. Companies that integrate environmental values into their corporate culture demonstrate higher success rates in implementing green strategies, while cultural resistance often impedes restructuring efforts. Leadership plays a crucial role in shaping sustainable practices by fostering ecological responsibility and guiding transformation processes. The study underscores the importance of aligning cultural frameworks with structural adaptations to ensure long-term sustainability success. Future research should focus on empirical validation, particularly in assessing the role of mid-level leadership in executing sustainability strategies.